The African diaspora a history through culture - Manning, Patrick (New York Columbia University Press, 2010)
Patrick Manning refuses to divide the African diaspora into the experiences of separate regions and nations. Instead, he follows the multiple routes that brought Africans and people of African descent into contact with one another and with Europe, Asia, and the Americas. In weaving these stories together, Manning shows how the waters of the Atlantic Ocean, the Mediterranean Sea, and the Indian Ocean fueled dynamic interactions among black communities and cultures and how these patterns resembled those of a number of connected diasporas concurrently taking shaping across the globe.
Includes bibliographical references and index.
Keywords: African diaspora --History.